2021
DOI: 10.22437/jini.v2i1.13519
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Kesiapsiagaan Masyarakat dalam Antisipasi Bencana Banjir Di Kecamatan Danau Kerinci Barat Kabupaten Kerinci

Abstract: Flood disaster is one of the biggest disasters in the world. It is hoped that the readiness and knowledge of the community in dealing with floods is expected to be proactive in being able to take preventive, emergency response and rehabilitation measures in collaboration with the government to maintain the environment that can cause flooding in order to minimize the impact it causes. The magnitude of the potential for flooding in Kerinci prompted the need for community preparedness measures to reduce losses du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…Public knowledge about disaster preparedness is seen from the community's understanding of the character of the surrounding flood disasters, cultural background, and the level of understanding of the community is safe in receiving information (Husna, 2012). The results of this study supported by Gustini, et al (2021), it can be concluded that the level of community preparedness in facing flood disasters in West Kerinci Lake District, Kerinci Regency is almost ready. Where the level of knowledge in the category is very well prepared.…”
Section: Analisis Bivariatsupporting
confidence: 72%
“…Public knowledge about disaster preparedness is seen from the community's understanding of the character of the surrounding flood disasters, cultural background, and the level of understanding of the community is safe in receiving information (Husna, 2012). The results of this study supported by Gustini, et al (2021), it can be concluded that the level of community preparedness in facing flood disasters in West Kerinci Lake District, Kerinci Regency is almost ready. Where the level of knowledge in the category is very well prepared.…”
Section: Analisis Bivariatsupporting
confidence: 72%
“…The majority were female, 175 people (68.1%), 91 people had a high school education (35%), and the majority of respondents occupation was housewife (housewife) 145 people (56.4%). The research results show that the highest percentage of community resource mobilization criteria is in the unfavorable criteria, namely 50.6%.Researchers found that many respondents still do not understand the importance of preparedness efforts, one of which is because they are rarely exposed to information regarding what can be done to reduce disaster risk, so it is important to provide education or socialization and preparedness training.A resource mobilization index value that is in the underprepared category is an indication of the lack or low capacity of individuals/communities in mobilizing their resources during and after a disaster occurs 11 . The community needs to be involved in overcoming disaster risks.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the community considers flood disasters as a habit that occurs routinely every rainy season. This is considered a regular flood because it is a habit that is thought to have occurred over a long period (Gustini, Subandi, and Oktarina 2021).…”
Section: Discussionmentioning
confidence: 99%